Removal of pharmaceuticals by novel magnetic genipin-crosslinked chitosan/graphene oxide-SO3H composite. (15th September 2019) - Liu, Yangshuo; Liu, Rong; Li, Ming; Yu, Fucheng; He, Chiyang
Highlights: 3D-GC/MGO-SO3 H demonstrates the high affinity to tetracycline. GC/MGO-SO3H show maximum adsorption capacity was 473.28 mg/g at 25 °C and pH 7. Adsorption capacity of GC/MGO-SO3H remained at 85% after five cycles. Abstract: A novel magnetic adsorbent genipin-crosslinked chitosan/ graphene oxide-SO3 H (GC/MGO-SO3 H) composite was prepared and used as adsorbents of environmental pollutant. The GC/MGO-SO3 H exhibit typical superparamagnetic behavior. The adsorption characteristics of GC/MGO-SO3 H composite to pharmaceuticals were investigated through batch experiments. The maximum adsorption capacity of ibuprofen and tetracycline increases from 113.27 to 138.16 mg/g and 473.25 to 556.28 mg/g with the increase in temperature from 298 to 313 K. The adsorption kinetics and isotherms were investigated in detail to reveal that the kinetics and equilibrium adsorptions are well described by pseudo-second-order kinetic and Freundlich isotherm model, respectively. This study has demonstrated that the GC/MGO-SO3 H composite could be utilized as an efficient and with high speed.